Synergy Among the Indonesia Maritime Security Institutions in Conducting Maritime Patrol - Haidul Firman Sitorus; Budiman Djoko Said (Jurnal Pertahanan: Media Informasi ttg Kajian & Strategi Pertahanan yang Mengedepankan Identity, Nasionalism & Integrity, 2023)
Maritime patrols are necessary because Indonesia is vulnerable to maritime threats and disturbances. Patrols are not optimally covered the sea and the regulations are not comprehensive to be synergy guidelines. This article discusses how to synergize effective and efficient patrols at the six maritime security institutions, and finally reduce the level of threats and disturbances to maritime security. This article uses qualitative methods and synergy models, interviews were conducted with informants from six maritime security institutions. Various elements of the patrol require collaboration consisting of personnel, assets, and ideas from various institutions. The advantages of an institution that should be utilized together include the size of the budget or assets, personnel militancy, social patrols, targeting patrols, aerial monitoring, and shipping court mechanisms. Trust exists from long-standing interactions to see competence and integrity, not by coercion of regulations. Leaders must meet all the criteria for leaders, both those who want strong criteria and those who want accountability or integrity or can accept criticism. Maritime patrol synergy is formed by the interaction of collaboration, engagement, trust components, and leadership support to ensure the synergy runs.